Remaking the Middle Ages the methods of cinema and history in portraying the medieval world - Elliott, Andrew B. R. (McFarland & Company, Inc., Publishers, 2011)
"Proposing a fresh theoretical approach to the study of cinematic portrayals of the Middle Ages, this book uses semiotics and historiography to demonstrate how contemporary filmmakers have attempted to recreate the past in a way that, while largely imagined, is also logical, meaningful, and as truthful as possible"--Provided by publisher.